2021
DOI: 10.3390/condmat7010004
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Compton Scattering Study of Li-Rich Battery Materials

Abstract: The redox process in a lithium-ion battery occurs when a conduction electron from the lithium anode is transferred to the redox orbital of the cathode. Understanding the nature of orbitals involved in anionic as well as cationic redox reactions is important for improving the capacity and energy density of Li-ion batteries. In this connection, we have obtained magnetic Compton profiles (MCPs) from the Li-rich cation-disordered rock-salt compound LixTi0.4Mn0.4O2 (LTMO). The MCPs, which involved the scattering of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Using X-ray Compton scattering in Li x Ti 0.4 Mn 0.4 O 2 , Hafiz et al [35] have confirmed the microscopic mechanism involving O-2p orbitals [112]. A similar conclusion was reached through magnetic X-ray Compton scattering study of Suzuki et al [36]. These studies, which involve a combination of X-ray Compton scattering experiments and parallel first principles modeling, have shown how electrons from Li atoms unleash electrical energy at the atomic level while occupying the redox orbitals at the active oxygen sites and how the electronic structure responds to Li intercalation.…”
Section: Case Study 3: Verwey Transition In the Limn 2 O 4 Spinel Bat...mentioning
confidence: 68%
See 2 more Smart Citations
“…Using X-ray Compton scattering in Li x Ti 0.4 Mn 0.4 O 2 , Hafiz et al [35] have confirmed the microscopic mechanism involving O-2p orbitals [112]. A similar conclusion was reached through magnetic X-ray Compton scattering study of Suzuki et al [36]. These studies, which involve a combination of X-ray Compton scattering experiments and parallel first principles modeling, have shown how electrons from Li atoms unleash electrical energy at the atomic level while occupying the redox orbitals at the active oxygen sites and how the electronic structure responds to Li intercalation.…”
Section: Case Study 3: Verwey Transition In the Limn 2 O 4 Spinel Bat...mentioning
confidence: 68%
“…BL08W employs linearly and elliptically polarized X-rays in the 100-300 keV range. It has been designed specifically for Compton scattering spectroscopy studies, including magnetic Compton scattering experiments [34,36] (Section 3.2), where measurements are performed at low temperatures with an external magnetic field of few teslas. The schematic of the BL08W beamline is shown in Figure 2b, see Refs.…”
Section: Experiments At the Spring-8 Synchrotron Facilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The computed energy loss function is consistent with RIXS experiments and displays a maximum related to the electronic states responsible for the redox potential of the LiNiO 2 cathode. Compton [43] and magnetic Compton [45] X-ray scattering studies will be valuable in providing an atomic level reconstruction of the redox orbitals of LNO.…”
Section: Discussionmentioning
confidence: 99%
“…[Location effects predicted here should be amenable to verification via magnetic Compton scattering experiments. 51,[66][67][68] ] SCAN has been successful in describing elemental Mn, which is a similar non-itinerant transition metal system. 45 Finally, we note that since correlation effects weaken directional bonding, DFT generally tends to underestimate the c/a ratio, which could be cured by including spin-orbit interactions and breaking symmetries around the iron atoms.…”
Section: Fe-4ementioning
confidence: 99%